2020
DOI: 10.3390/su12155890
|View full text |Cite
|
Sign up to set email alerts
|

Objectively-Assessed Physical Activity, Sedentary Behavior, Smartphone Use, and Sleep Patterns Pre- and during-COVID-19 Quarantine in Young Adults from Spain

Abstract: This study assessed the effects of COVID-19 home confinement on physical activity, sedentary behavior, smartphone use, and sleep patterns. Data was collected in a sample of 20 young adults (mean age ± SD: 22.6 ± 3.4 years; 55% males) over seven days pre- and during the COVID-19 lockdown. Objective and subjective physical activity (Accelerometer and the International Physical Activity Questionnaire (IPAQ), respectively), the number of hours sitting (IPAQ), objectively-measured smartphone use (smartphone screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
179
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(206 citation statements)
references
References 50 publications
18
179
3
6
Order By: Relevance
“…Romero-Blanco et al ( 2020 ) showed that Health Sciences university students performed significantly higher minutes/week of total PA (+71.6%) and vigorous PA (+7.4%), both males (+ 83.3%) as females (+ 23.6%). On the other hand, Sañudo et al ( 2020 ) showed an objective reduction in PA with 67.7% fewer steps per day during the lockdown. In the same line, five studies showed a reduction of light/mild PA (walking) between 32.5 and 365.5% compared to the period prior to confinement (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Sañudo et al, 2020 ), three studies found a decrease in moderate PA levels (from 14–59.7%) (Barkley et al, 2020 ; Gallè et al, 2020 ; Sañudo et al, 2020 ) and four studies in moderate-to-vigorous PA (MVPA) (from 3.9–56.6%) (Karuc et al, 2020 ; Maher et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Romero-Blanco et al ( 2020 ) showed that Health Sciences university students performed significantly higher minutes/week of total PA (+71.6%) and vigorous PA (+7.4%), both males (+ 83.3%) as females (+ 23.6%). On the other hand, Sañudo et al ( 2020 ) showed an objective reduction in PA with 67.7% fewer steps per day during the lockdown. In the same line, five studies showed a reduction of light/mild PA (walking) between 32.5 and 365.5% compared to the period prior to confinement (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Sañudo et al, 2020 ), three studies found a decrease in moderate PA levels (from 14–59.7%) (Barkley et al, 2020 ; Gallè et al, 2020 ; Sañudo et al, 2020 ) and four studies in moderate-to-vigorous PA (MVPA) (from 3.9–56.6%) (Karuc et al, 2020 ; Maher et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…One thousand one hundred thirty-seven references were identified after search process in four databases, of which 10 (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Karuc et al, 2020 ; Maher et al, 2020 ; Romero-Blanco et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ; Alarcón Meza and Hall-López, 2021 ) met the inclusion criteria. Figure 1 shows the flow chart of the selection process of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the Spring 2020 pandemic, engaging in active behaviours was particularly relevant to counteracting the detrimental effects of lockdown (Lesser & Nienhuis, 2020). Yet, a fast-growing literature reveals that individuals' PA behaviours were altered during this period: while most individuals decreased their engagement in PA, a portion of the population increased it (Cheval et al, 2020;Constandt et al, 2020;Deschasaux-Tanguy et al, 2020;Gallè et al, 2020;Sañudo et al, 2020).…”
Section: Lockdownmentioning
confidence: 99%
“…During this "window of opportunity", individuals are prone to engage in deliberative processes, leading to the renegotiation of previous behaviours (Verplanken & Roy, 2016). This discontinuity hypothesis may thus explain why some studies observed an increase of PA behaviours during lockdown (Cheval et al, 2020;Constandt et al, 2020; but see Deschasaux-Tanguy et al, 2020;Gallè et al, 2020;Sañudo et al, 2020 for contradictory findings).…”
Section: Association Of Pa Behaviours With the Evolution Of Pa Habitsmentioning
confidence: 99%